Prevention of healthcare-associated infections in neonates: room for improvement. Issue 4 (April 2015) - Legeay, C.; Bourigault, C.; Lepelletier, D.; Zahar, J.R.
Summary Infants in neonatal intensive care units (NICUs) are highly susceptible to infection due to the immaturity of their immune systems. Healthcare-associated infections (HCAIs) are associated with prolonged hospital stay, and represent a significant risk factor for neurological development problems and death. Improving HCAI control is a priority for NICUs. Many factors contribute to the occurrence of HCAIs in neonates such as poor hand hygiene, low nurse–infant ratios, environmental contamination and unnecessary use of antibiotics. Prevention is based on improving neonatal management, avoiding unnecessary use of central venous catheters, restricting use of antibiotics and H2 blockers, and introducing antifungal prophylaxis if necessary. Quality improvement interventions to reduce HCAIs in neonates seem to be the cornerstone of infection control.